Dihydroartemisinin Exerts Anti-Tumor Activity by Inducing Mitochondrion and Endoplasmic Reticulum Apoptosis and Autophagic Cell Death in Human Glioblastoma Cells - Qu, Chengbin; Ma, Jun; Liu, Xiaobai; Xue, Yixue; Zheng, Jian; Liu, Libo; Liu, Jing; Li, Zhen; Zhang, Lei; Liu, Yunhui (Frontiers in Cellular Neuroscience, 2017)
Glioblastoma (GBM) is the most advanced and aggressive form of gliomas. Dihydroartemisinin (DHA) has been shown to exhibit anti-tumor activity in various cancer cells. However, the effect and molecular mechanisms underlying its anti-tumor activity in human GBM cells remain to be elucidated. Our results proved that DHA treatment significantly reduced cell viability in a dose- and time-dependent manner by CCK-8 assay. Further investigation identified that the cell viability was rescued by pretreatment either with Z-VAD-FMK, 3-MA or in combination. Moreover, DHA induced apoptosis of GBM cells through mitochondrial membrane depolarization, release of cytochrome c and activation of caspases-9. Enhanced expression of GRP78, CHOP and eIF2α, and activation of caspase 12 were additionally confirmed that endoplasmic reticulum (ER) stress pathway of apoptosis was involved in the cytotoxicity of DHA. DHA-treated GBM cells exhibited the morphological and biochemical changes typical of autophagy. Co-treatment with chloroquine (CQ) significantly induced the above effects. Furthermore, ER stress and mitochondrial dysfunction were involved in the DHA-induced autophagy. Further study revealed that accumulation of reactive oxygen species (ROS) was attributed to the DHA induction of apoptosis and autophagy. The illustration of these molecular mechanisms will present a novel insight for the treatment of human GBM.